Illumination on the structure and characteristics of Entamoeba histolytica genome. - Musafer Al-Ardi (Al-Qadisiyah Journal of Pure Science, 2021)
Entamoeba histolytica, likes other Organismes, is characterized by diversity and heterogeneity in its genetic content, which is one of the most paramount reasons for survival, and the increase in susceptibility to infection. Non-condensation of chromosomes during the process of cell division and the ambiguity of the chromosomal ploidy makes predicting the exact chromosomal numeral difficult. Genes distributed across 14 chromosomes as well as many extra-chromosome elements. Most Genes compose of one axon only, with Introns in 25% of Genes. This genome is characterized by the presence of Polymorphic internal repeat regions, and several gene families, one of these large families encoding Transmembrane kinas, Cysteine protease (CP), SREHP protein, and others.